Pastiche in Contemporary Latin American Literature - Jean Franco (Studies in 20th & 21st Century Literature, 1990)
Pastiche, defined as non-satiric imitation, is a characteristic feature of contemporary Latin American narrative. Although unlike parody it does not stand in antagonist relationship with a prior text, nevertheless pastiche marks a distance and a displacement of other texts. The article illustrates this with reference to Mario Vargas Llosa's pastiche of Machiguenga indigenous legends in his novel El hablador and Silviano Santiago's pastiche of Graciliano Ramos's prison memories in his novel, Em Liberdade.
Keywords: Contemporary Latin American literature; Pastiche; non-satiric imitation; narrative; distance; displacement; Mario Vargas Llosa; Machinguenga indigenous legends; El hablador; Silviano Santiago; Graciliano Ramos; prison memories; Em Liberdade